(untitled) (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2025)
This article examines infectious diseases of the visual organ, their etiology, clinical symptoms, diagnostic methods, and modern treatment approaches. Eye infections are most often caused by bacteria, viruses, fungi, and parasites. The article analyzes common infections such as conjunctivitis, keratitis, and blepharitis, as well as the treatments applied for their diagnosis and management.